Bundle 4 diversified integrated mixed chicken/goats – legume systems: Legume Value Chains; Changing Lives, Protecting Nature - Community Markets for Conservation (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Community Markets for Conservation (COMACO) is a social enterprise that finances improved agricultural practices through the adoption of agroforestry and a legume-based farming system that increases food crop yields and market opportunities for over 230,000 small-scale farmers. The proposed project will build on this foundation that spans 19 years of growing a brand called It’s Wild! of 20 different value-added food products by partnering with the Chitetezo Co-operative Federation. Through this partnership, COMACO will expand its impact on sustainable agriculture adoption and the various ways these practices can increase conservation outcomes, including reduced deforestation and dependencies on such livelihoods as charcoal-making and wildlife poaching. COMACO aims to strengthen the Federation, which represents 55 farmer cooperatives in Eastern Province, to help improve the cost-efficiency of its community-based supply chain of legumes by enhancing cooperative leadership to address such challenges as grain quality, crop bulking, transport logistics, and local adoption of mobile banking. This partnership will also help achieve increased gender role in cooperative leadership, commitment to community-agreed conservation regulations for soil and forest protection, cooperative-run services to support farmer training and local seed production and improved financial sustainability of COMACO. The Federation’s management team will engage cooperative leaders to build a stronger commercial relationship with COMACO by achieving the following deliverables: 1) 80% farmer adoption of agroforestry, 2) cooperative seed growers supporting 50% of local legume seed requirements, 3) 20% increase in cooperative leadership positions held by women, and 4) 30% increase in women farmers selling legumes to COMACO